(untitled) (Research, Society and Development, 2020)
This paper presents a clipping of a master’s dissertation aiming to investigate how students build scientific knowledge using the methodology of experimentation in Chemistry Teaching and to analyze the strategies, potentialities and limitations of this methodology in High School. The theoretical framework addresses pedagogical and epistemological questions of experimentation. The intervention for this investigation was carried out in a public school of Basic Education, located in the municipality of Vila Nova do Sul / RS, with students of the first year of high school. The research methodology used the qualitative approach and from the production of data emerged categories of analysis. As a result of this research it is pointed out that students have become more independent as they carry out the experiments, with frequent questions during the class, while making important decisions in the development of the experiments.